2015
DOI: 10.3758/s13423-015-0825-4
|View full text |Cite
|
Sign up to set email alerts
|

Three symbol ungrounding problems: Abstract concepts and the future of embodied cognition

Abstract: A great deal of research has focused on the question of whether or not concepts are embodied as a rule. Supporters of embodiment have pointed to studies that implicate affective and sensorimotor systems in cognitive tasks, while critics of embodiment have offered nonembodied explanations of these results and pointed to studies that implicate amodal systems. Abstract concepts have tended to be viewed as an important test case in this polemical debate. This essay argues that we need to move beyond a pretheoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 161 publications
(194 reference statements)
3
100
0
7
Order By: Relevance
“…In other words, it is true by casual observation that human conceptual processing can flexibly recombine information essentially ad infinitum —the properties of the human mind that make this possible have been the topic of much theoretical work (e.g., Chomsky, 1959; Fodor, 1975, Pinker, 1994; Barsalou, 1999). Recent emphasis of ‘flexibility in concept representation’ is focused instead on the idea that concepts (i.e., the ‘representations themselves’) are dynamic with dissociable components, such that one aspect of a ‘concept’ may be used in one context or task, while another aspect of the concept may be used in another (Willems and Casasanto, 2011; Van dam et al, 2012; for discussion, see Dove, this issue; Kemmerer, this issue; Yee and Thompson-Schill, this issue). In other words, concepts do not have cores that are retrieved each time a concept is tokened: overlapping subsets of conceptual information, that collectively form the ‘full’ concept, can be solicited in a flexible manner according to task constraints.…”
Section: Some Major Themes From This Volume and Their Broader Implicamentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, it is true by casual observation that human conceptual processing can flexibly recombine information essentially ad infinitum —the properties of the human mind that make this possible have been the topic of much theoretical work (e.g., Chomsky, 1959; Fodor, 1975, Pinker, 1994; Barsalou, 1999). Recent emphasis of ‘flexibility in concept representation’ is focused instead on the idea that concepts (i.e., the ‘representations themselves’) are dynamic with dissociable components, such that one aspect of a ‘concept’ may be used in one context or task, while another aspect of the concept may be used in another (Willems and Casasanto, 2011; Van dam et al, 2012; for discussion, see Dove, this issue; Kemmerer, this issue; Yee and Thompson-Schill, this issue). In other words, concepts do not have cores that are retrieved each time a concept is tokened: overlapping subsets of conceptual information, that collectively form the ‘full’ concept, can be solicited in a flexible manner according to task constraints.…”
Section: Some Major Themes From This Volume and Their Broader Implicamentioning
confidence: 99%
“…In this regard, the patient data have formed an important part of the motivation for ‘hybrid’ accounts: on these accounts, while conceptual processing reaches into the sensorimotor systems, the center of gravity of conceptual processing is abstracted away from specific sensorimotor information, and distributed across many systems. A number of contributions in the current volume fall into this ‘hybrid’ class of proposals (Binder, this issue; Jamrozik et al, this issue; Kemmerer, this issue; Reilly et al, this issue; Zwaan, this issue; see also Dove, this issue; Hickok, 2014; Mahon and Caramazza, 2008). One generalization that emerges across this volume – which is a good trope for the broader field – is that there is general recognition that simple oppositions of ‘are concepts this or that’ do not capture the subtleties that are demanded of any reasonably sufficient theory.…”
Section: Background and Introduction To The Questionmentioning
confidence: 99%
“…Of course, no one would deny that context influences conceptual processing – decades of semantic priming studies have shown just this (e.g., Barclay, Bransford, Franks, McCarrell & Nitsch, 1974; Meyer & Schvaneveldt 1971; Tabossi, 1988), and several authors have considered context effects and/or conceptual flexibility in the context of evaluating sensorimotor-based (or “embodied”) theories of conceptual representation (e.g., Dove, 2015; Hauk & Tschentscher, 2013; Kiefer & Pulvermuller, 2012; Mahon, 2015) and language processing (Taylor & Zwaan, 2009; Willems & Casasanto, 2011). Our point is not simply that conceptual access changes with context.…”
Section: (0) Introductionmentioning
confidence: 99%
“…Indeed, combination between CFDs can give rise to a more complex CFD, defined for instance as the structural combination of several elements (think, e.g., of a triangle, as composed of three segments correctly arranged). The combination might also refer to a taxonomic level (generalization; Dove, 2016), such as, for instance, when the combination of CFDs for various known cat breeds or types would give rise to a generic cat CFD.…”
Section: Precisions On Complexity / Abstractnessmentioning
confidence: 99%